2008
DOI: 10.1002/chem.200800524
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Larger Hydrocarbons in the Ionosphere of Titan

Abstract: Among the many fascinating results of the Cassini-Huygens mission, the mass spectrum of the ionosphere of Titan has attracted considerable attention. [1] In brief, the ionosphere was found to be surprisingly complex, consisting of hydrocarbon ions C m H n + as well as nitrogen-containing ions C n H n N o + with mass-to-charge ratios up to the probes limit of m/z 100; [2] even much heavier components have been proposed. [1b, 3] While the formation of C m H n compounds with m 7 is reasonably well understood, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

8
1

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 45 publications
0
52
0
2
Order By: Relevance
“…Thus, fragmentation to another dication and a neutral fragment is usually energetically disfavored [6]. Nevertheless, for hydrocarbon dications, it was shown that bond-forming reactions where twofold charge is preserved can represent the dominant reactivity channel [12,13]. The trick involves opening a low energy exit channel denoted by elimination of an H atom of a H 2 molecule [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, fragmentation to another dication and a neutral fragment is usually energetically disfavored [6]. Nevertheless, for hydrocarbon dications, it was shown that bond-forming reactions where twofold charge is preserved can represent the dominant reactivity channel [12,13]. The trick involves opening a low energy exit channel denoted by elimination of an H atom of a H 2 molecule [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The precursor dications in these studies were generated by electron ionization, which is known as a "hard" ionization method. For reference purposes, in these previous studies we also investigated the unimolecular fragmentations of the metastable reactant dications, as well as their fragmentation in the presence of rare gases as, supposedly, chemically inert collision partners.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Most of these reactions are driven by the radicaloid nature of the oxide cations with the spin mostly located on oxygen, which leads to a high preference for hydrogen-atom abstraction from methane to generate methyl radicals. This situation is in contrast to the dehydrogenation of methane by various 5d elements to give metal carbenes MCH 2 + , [6,11] or MCH 2 2+ , [6,12] and to the C À C coupling reactions with methane observed for medium-sized hydrocarbon dications, [13] in which the dehydrogenation takes place with the "CH 2 " fragment remaining at the ionic species.…”
mentioning
confidence: 56%